2018
DOI: 10.1159/000486041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Magnetic Resonance Imaging/Ultrasound-Fusion Biopsy in Patients with Low-Risk Prostate Cancer Under Active Surveillance Undergoing Surveillance Biopsy

Abstract: Introduction: Targeted biopsy of tumour-suspicious lesions detected in multiparametric magnetic resonance imaging (mpMRI) plays an increasing role in the active surveillance (AS) of patients with low-risk prostate cancer (PCa). The aim of this study was to compare MRI/ultrasound-fusion biopsy (fusPbx) with systematic biopsy (sysPbx) in patients undergoing biopsy for AS. Methods: Patients undergoing mpMRI and transperineal fusPbx combined with transrectal sysPbx (comPbx) as surveillance biopsy were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“… Reference ID Study design Sample size Mean age (SD) Definition of low-risk prostate cancer Quality assessment Chen/2018/Singapore [ 27 ] Prospective cohort 19 65.4 (4.9) prostate specific antigen (PSA) ≤10 ng/mL, Gleason score ≤6, clinical stage ≤ T2a) Fair Alberts/2017/Netherlands [ 28 ] Prospective cohort 210 65.4# Gleason score 3 + 3 Fair Almeida/2016/Italy [ 29 ] Prospective cohort 73 63 (5.9) 1) men should have a histologically proven adenocarcinoma of the prostate, and they should be fit for possible curative treatment, be willing to attend the follow-up visits, and should not have received former therapy [ 2 ]; clinical stage T1c/T2 [ 3 ]; GS ≤ 6 [ 4 ]; ≤ 2 positive biopsy cores [ 5 ]; PSA ≤ 10 ng/mL [ 6 ]; PSAD ≤ 0.2 ng/mL/ml. Fair Borkowetz/2017/Germany [ 30 ] Retrospective cohort 83 73# ≤cT2c, ≤2 cores with proven cancer, Gleason score ≤6 (3 + 3), prostate specific antigen (PSA) density <0.2 ng/mL2 and PSA <10 ng/mL. Fair Hamoen/2018/Netherlands [ 31 ] Prospective cohort 111 64# PSA density <0.2 ng/mL/ml, clinical stage cT1c–cT2c, and GS 3 + 3 and 2 positive biopsy cores at initial TRUSGB were Fair Hashimoto/2012/Japan [ 32 ] Retrospective cohort 11 65# NR …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Reference ID Study design Sample size Mean age (SD) Definition of low-risk prostate cancer Quality assessment Chen/2018/Singapore [ 27 ] Prospective cohort 19 65.4 (4.9) prostate specific antigen (PSA) ≤10 ng/mL, Gleason score ≤6, clinical stage ≤ T2a) Fair Alberts/2017/Netherlands [ 28 ] Prospective cohort 210 65.4# Gleason score 3 + 3 Fair Almeida/2016/Italy [ 29 ] Prospective cohort 73 63 (5.9) 1) men should have a histologically proven adenocarcinoma of the prostate, and they should be fit for possible curative treatment, be willing to attend the follow-up visits, and should not have received former therapy [ 2 ]; clinical stage T1c/T2 [ 3 ]; GS ≤ 6 [ 4 ]; ≤ 2 positive biopsy cores [ 5 ]; PSA ≤ 10 ng/mL [ 6 ]; PSAD ≤ 0.2 ng/mL/ml. Fair Borkowetz/2017/Germany [ 30 ] Retrospective cohort 83 73# ≤cT2c, ≤2 cores with proven cancer, Gleason score ≤6 (3 + 3), prostate specific antigen (PSA) density <0.2 ng/mL2 and PSA <10 ng/mL. Fair Hamoen/2018/Netherlands [ 31 ] Prospective cohort 111 64# PSA density <0.2 ng/mL/ml, clinical stage cT1c–cT2c, and GS 3 + 3 and 2 positive biopsy cores at initial TRUSGB were Fair Hashimoto/2012/Japan [ 32 ] Retrospective cohort 11 65# NR …”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, the biopsy scheme did not have a significant effect on the upstaging rates, even with the combination of targeted and systematic biopsies [ 11 ]. Borkowetz et al reported similar results for combination biopsies, where a combination of MRI/ultrasound-fusion biopsy and systematic biopsy, in patients undergoing AS for prostate cancer, outperformed both modalities alone [ 30 ]. The combination scheme detected upgrading in 71% if the patients compared to 64% and 59% of MRI/ultrasound-fusion and systematic biopsies, respectively [ 30 ].…”
Section: Role Of Multiparametric Magnetic Resonance Imaging (Mpmri) Imentioning
confidence: 97%
See 1 more Smart Citation
“…The ethnic difference or small study population might be the reasons for these study results. Likewise, MRI evaluations for AS candidates were passionate [31,32]. Further investigation is needed for the future study.…”
Section: Discussionmentioning
confidence: 99%
“…This integrated system arose from the recently growing demand for the development of bio‐optical imaging systems that can obtain complementary, vital tissue information and improve tissue characterization . In conventional medical imaging, the fusion of PET with CT (PET‐CT) , or with MRI (PET‐MRI) , and MRI with ultrasound (MRI‐US) are examples of this approach and have brought about a revolution in the medical world, tremendously advancing our understanding of the function and physiology of human organs. Similarly, researchers have taken advantage of the significant advantages of using light (low‐cost, ease of operation, portability, and lack of ionizing radiation) and combined optical tissue monitoring and imaging techniques with conventional medical instruments in multiple fields of medicine to provide complementary structural and functional physiological information.…”
Section: Introductionmentioning
confidence: 99%